Optimization of wavelet based OFDM for multipath powerline channel by genetic algorithm - Kumbasar, Volkan; Kucur, Oğuz; Ergin, A. Arif; Ozturk, Ertan (Wiley-Hindawi, 2009)
Using genetic algorithm (GA), optimal wavelets are obtained to reduce ISI and ICI powers of a wavelet-based orthogonal frequency division multiplexing (OFDM) system over a practical two path low-voltage powerline channel or two path fading channel by relaxing the perfect quadrate mirror filter (QMF) orthogonality. Optimum wavelet-based OFDM system experiences less interference compared to conventional and Daubechies (Db) wavelet-based OFDM systems. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: OFDM; wavelets; genetic algorithm; ISI; ICI; optimization